Bahasa Inggris - Aurilia Triani Aryaningtyas; Aletta Dewi Maria Th; Yustina Denik Risyanti (Jurnal Ilmu Sosial dan Humaniora, 2024)
This study investigates the dynamics of community engagement and resilience within Indonesia's tourism sector during the COVID-19 pandemic. It adopts a qualitative methodology, with document analysis as the primary technique. Publicly accessible documents, including news reports, journal articles, and policy briefs, are compiled and systematically analyzed using content analysis. The study extracts key themes and strategies local communities use to sustain involvement and enhance resilience during the crisis. Data from multiple sources are triangulated to validate findings and provide a comprehensive perspective. The research uncovers innovative approaches such as digital transformation, collaborative networks, health protocols, and public-private partnerships employed by communities to adapt to pandemic challenges. It highlights efforts to engage communities, preserve culture, promote eco-tourism, and foster social entrepreneurship to aid tourism recovery. The study offers insights that can inform strategies for strengthening community participation, resilience, and sustainability in Indonesian and global tourism as the world emerges from the pandemic. Elucidating community engagement and resilience dynamics contributes critical perspectives to guide policymakers and practitioners in future-proofing tourism against crises.